1979
DOI: 10.1139/z79-293
|View full text |Cite
|
Sign up to set email alerts
|

Temperature regulation in freely diving harp seals (Phoca groenlandica)

Abstract: Measurements were made of the relation between body temperature, respiration, diving pattern, and water temperature using three adult harp seals (Phoca groenlandica). Core temperature, ventilation, gas exchange, and diving pattern were not affected by water temperature ranging from 1.8 to 28.2 °C. The basal metabolic rate of the seals in this study was not significantly different than that predicted for terrestrial mammals of equivalent size. Expired heat loss and convective heat loss from the body accounted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 22 publications
4
38
1
Order By: Relevance
“…Young phocids have a significantly thicker and better quality (higher lipid content) blubber layer compared with young otariids (Mostman Liwanag, 2008). Accordingly, juvenile harp seals and harbor seals appear to be thermally competent in the range of water temperatures often encountered by adults in the wild (Hart and Irving, 1959;Gallivan and Ronald, 1979). This contrasts with young otariids, which appear to exhibit reduced thermal capabilities (compared with adults) during the period of transition to independent living.…”
Section: Thermal Limitations In Juvenile Sea Lionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Young phocids have a significantly thicker and better quality (higher lipid content) blubber layer compared with young otariids (Mostman Liwanag, 2008). Accordingly, juvenile harp seals and harbor seals appear to be thermally competent in the range of water temperatures often encountered by adults in the wild (Hart and Irving, 1959;Gallivan and Ronald, 1979). This contrasts with young otariids, which appear to exhibit reduced thermal capabilities (compared with adults) during the period of transition to independent living.…”
Section: Thermal Limitations In Juvenile Sea Lionsmentioning
confidence: 95%
“…Thus, a relationship between T LC and oceanic movements exists for phocid seals, such that species occupy, and may be limited to, ranges that enable them to maintain minimum resting metabolic rates in the wild (Hart and Irving, 1959;Gallivan and Ronald, 1979). With a T LC below 0°C, harp seals (Phoca groenlandica) can maintain basal metabolic rates at temperatures several degrees below environmental temperatures (Gallivan and Ronald, 1979) whereas harbor seals alter movements seasonally to remain in water temperatures close to their exact T LC (Hart and Irving, 1959). In comparison, California sea lions range from Washington to Mexico (adult females: California to Mexico), where sea surface temperatures can range from approximately 5 to 30°C (female range: 10-30°C) (Rice, 1998;Reeves et al, 2002) …”
Section: Thermal Capabilities Of the California Sea Lionmentioning
confidence: 99%
“…Heat loss from the appendages can be controlled by blood flow to the flippers, where vascular countercurrent heat exchangers that prevent excessive heat loss under cold conditions can be occluded when heat dissipation is necessary (Tarasoff and Fisher, 1970). Gallivan and Ronald (1979) indicated that 84% of heat loss from harp seals (Phoca groenlandica) was lost from the flippers. Ryg et al (1993) assumed that 15-25% of the total heat loss of a resting seal in water is lost by free convection from the appendages and that this value can increase to 66-77% during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…D: In phocid seals, the superficial veins from the hind flipper, which dive deep within the body near the tail rather than follow the hind limb, feed cooled venous blood to internal plexuses before joining the vena cava (after Rommel et al, 1995). Superficial branches of the deep circumflex iliac vein may exist in seals; however, the hind flipper has been show to be a major site of heat loss in phocid seals (Galivan and Ronald, 1979). [Color figure can be viewed in the online issue, which is available at www.interscience.…”
Section: Discussionmentioning
confidence: 99%
“…5C). The internal plexus of the seal is supplied by cooled blood from the hind flippers, which have been shown to be a major site of heat loss (Galivan and Ronald, 1979). It is not yet known whether superficial branches of the deep circumflex iliac vein in the seal feed into the plexuses that cool the reproductive organs.…”
Section: Evolutionary Implicationsmentioning
confidence: 99%